2017
DOI: 10.1002/hon.2383
|View full text |Cite
|
Sign up to set email alerts
|

Brentuximab vedotin in relapsed/refractory Hodgkin lymphoma. The Hellenic experience

Abstract: This retrospective study aimed to describe the Hellenic experience on the use of brentuximab vedotin (BV) in relapsed/refractory (R/R) Hodgkin lymphoma (HL) given within its indication. From June 2011 to April 2015, ninety‐five patients with R/R HL, who received BV in 20 centers from Greece, were analyzed. Their median age was 33 years, and 62% were males. Sixty‐seven patients received BV after autologous stem cell transplantation failure, whereas 28 patients were treated with BV without a prior autologous ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 31 publications
(102 reference statements)
1
35
0
4
Order By: Relevance
“…The results of this study led to the accelerated Food and Drug Administration (FDA) approval of BV in 2011. Although these results have been reproduced by other studies, the impact of BV on the overall survival (OS) of patients with R/R cHL has not been addressed so far . In this study, we present data obtained from 214 patients with R/R HL after auto‐SCT reported in the Greek registry.…”
Section: Introductionmentioning
confidence: 60%
“…The results of this study led to the accelerated Food and Drug Administration (FDA) approval of BV in 2011. Although these results have been reproduced by other studies, the impact of BV on the overall survival (OS) of patients with R/R cHL has not been addressed so far . In this study, we present data obtained from 214 patients with R/R HL after auto‐SCT reported in the Greek registry.…”
Section: Introductionmentioning
confidence: 60%
“…До 5 % пациентов с полным ответом после терапии БВ (от 5 до 11 пациентов [17,18]) остаются в ремиссии без какого-либо последующего ле-чения. В базовом исследовании сообщается о 9 (9 %) таких пациентах [6].…”
Section: Discussionunclassified
“…Показатели эффективности БВ у пациентов с р / р CD30-положительной ЛХ после как минимум 2 линий предшествующей терапии в случаях, когда аутоТГСК и комбинированная химиотерапия не рассматриваются как вариант терапии, из обзора Европейского агентства по лекарственным средствам [27] Показатели Все пациенты (n=59), чел. (%) Наибольшее число публикаций было найдено для сме-шанной популяции -13 публикаций: 10 из них о про-грамме дорегистрационного использования препарата по запросу врача (Named Patient Program, NPP) в разных странах: Франция [16,23,25], Италия [19], Германия [21], Турция [20], Азия [26], Греция [18], в том числе 2 система-тических обзора [11,12], 2 публикации по применению БВ в Италии после окончания NPP [17,22], а также 1 систе-матический обзор и мета-анализ [10]. Все исследования, кроме систематических обзоров, имеют уровень доказа-тельности С как ретроспективные несравнительные иссле-дования.…”
Section: эффективность терапии брентуксимабом ведотином у разных попуunclassified
See 2 more Smart Citations